2005
DOI: 10.1111/j.1471-4159.2005.03570.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased GTP‐stimulated adenylyl cyclase activity in HPRT‐deficient human and mouse fibroblast and rat B103 neuroblastoma cell membranes

Abstract: Defect of the purine salvage enzyme, hypoxanthine phosphoribosyl transferase (HPRT), results in Lesch-Nyhan disease (LND). It is unknown how the metabolic defect translates into the severe neuropsychiatric phenotype characterized by self-injurious behavior, dystonia and mental retardation. There are abnormalities in GTP, UTP and CTP concentrations in HPRT-deficient cells. Moreover, GTP, ITP, XTP, UTP and CTP differentially support G s -protein-mediated adenylyl cyclase (AC) activation. Based on these findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…In mouse fibroblasts, NTPDase 3 expression decreased, whereas NTPDase 4-6 expression actually increased. Thus, our present expression data for individual NTPDase isoenzymes confirm the notion that secondary biochemical changes in HPRT-deficiency are cell type-and species-specific [12,11].…”
supporting
confidence: 75%
See 2 more Smart Citations
“…In mouse fibroblasts, NTPDase 3 expression decreased, whereas NTPDase 4-6 expression actually increased. Thus, our present expression data for individual NTPDase isoenzymes confirm the notion that secondary biochemical changes in HPRT-deficiency are cell type-and species-specific [12,11].…”
supporting
confidence: 75%
“…Similar to LND patients, there are abnormalities in dopaminergic neurotransmission in the HPRT knock-out mouse [7,16]. In addition, several HPRT-deficient cell lines including primary human skin fibroblasts, immortalized mouse skin fibroblasts, mouse Neuro2a neuroblastoma cells and rat B103 neuroblastoma are used as biochemical models for LND [18,2,4,12,11]. In a recent study [11] we showed that nucleoside 5 -triphosphatase (NTPase) activity in B103-and Neuro2a cell membranes is reduced in HPRT-deficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we examined AC regulation in membranes of B103 control and HPRT − cells (Pinto and Seifert 2006). Compared with control membranes, in HPRT − membranes, AC activities under basal conditions and in the presence of guanosine triphosphate (GTP) were substantially decreased.…”
mentioning
confidence: 98%
“…In HPRT-deficient cells, 6-thioguanine cannot be converted to the cytotoxic 6-thioguanosine 5′-triphosphate and hence, cells survive (Zoref-Shani et al 1993;Hacke et al 2012). HPRTdeficient B103 cells are an established cell culture model for LND and have already been used for two decades to study various aspects of the pathophysiology of LND including alterations in neuronal differentiation, nucleotide metabolism, purinoceptor function, nucleotidase activity, nucleotidase gene expression, and adenylyl cyclase (AC) regulation (Zoref-Shani et al 1993;Ma et al 2001;Connolly 2001;Pinto et al 2005;Pinto and Seifert 2006;Lorenz et al 2007;Erdorf et al 2011a).…”
mentioning
confidence: 99%